Crystallization conditions and magmatic evolution of the Pedra Branca syenite based on the chemistry of accessory minerals - Gonzaga, Victor Brugnera Camassari de (2022)
The Pedra Branca Syenite, located in the southern portion of the Guaxupé Domain, is a Neoproterozoic pluton (594±6 Ma) comprised of four main syenitic units, each with distinct mineralogical characteristics, but similar chemical compositions. To better understand the origin of the mineralogical variation, a detailed study was proposed regarding the crystallization conditions, specifically temperature and oxygen fugacity (fO2), which controlled the development of each unit. As the accessory phases are abundant in all units of the Pedra Branca pluton, and they record the main stages of crystallization (early-, main- and late-stage), it was decided to carry out the characterization of both the crystallization temperatures and the oxygen fugacity based on the chemistry of accessory minerals, namely, apatite, titanite and zircon. To characterize the crystallization temperatures, two different geothermometers were used; Ti in zircon (Ferry & Watson, 2007) and Zr in titanite (Hayden et al 2008). Zircon crystallization temperatures between 750ºC and 800ºC were obtained for the silica-saturated laminated syenites (LSS unit) and 870ºC to 950ºC for the silica-supersaturated syenite units. In contrast, titanite crystallization temperatures are higher (820-860ºC) in the LSS unit, and lower (720-780ºC) in supersaturated syenites, where this mineral is interstitial, occurring as an overgrowth of Fe-Ti oxides. For the characterization of oxygen fugacity, the Ce in zircon geobarometer (Smythe and Brenan, 2016) and the lattice strain model, were adopted. Based on the results obtained it was possible to determine that the Pedra Branca pluton records increasingly more oxidizing conditions towards the border of the pluton, with values around the NNO+1 and NNO+2, whereas the oversaturated units present around the core of the pluton record values around the NNO buffer. From the results obtained it was possible to determine that the different units of the Pedra Branca pluton record different crystallization conditions, which can explain the mineralogical differences observed in the pluton.